(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the clinical pattern and endometrial pathology of abnormal uterine bleeding among perimenopausal women. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Hamdard University Hospital, Karachi from July 2019 to December 2020. Materials and Methods: 105 perimenopausal women between 40-50 years of age who presented with abnormal uterine bleeding (AUB), and underwent dilatation and curettage for endometrial sampling were enrolled in this study after informed consent. A detailed clinical assessment of patients performed in the outpatient department; included history and clinical examination. Patients' medical records were evaluated for parameters including age, parity, clinical presentation and ultrasound findings. Histopathology evaluation was done by histopathologists. Results: 57.1% participants were of age between 40-45 years, and 58.1% women were Multiparous. Pattern of uterine bleeding in perimenopausal women about 66.7%, women had frequent menstrual cycle and prolonged duration of bleeding 78.1%, history of heavy bleeding with clots, in 22.9%, 5.7% and 14.3% women had complaint of inter-menstrual, premenstrual and breakthrough bleeding respectively. 59% patients had more than 18 mm endometrial thickness. Proliferative endometrium was the most prevalent diagnosis 39% followed by secretory endometrium 31.4%, hyperplasia without atypia 11.4%, polyp 10.5%, endometritis 2.9%, hyperplasia with atypia 2.9% and 1.9% patients diagnosed with cancer. Factors like parity, pattern of bleeding, US findings and endometrial thickness had significant impact on different types of histopathology (P-value<0.05). Conclusion: This study emphasises the need of endometrial sampling as an important diagnostic tool that would help in individualising the management of abnormal uterine bleeding with a view to reduce unnecessary benign hysterectomy procedures.